Effect of Intravitreal Bevacizumab in Macular Edema Caused by Branch Retinal Vein Occlusion - Irfan Aslam Khattak, Imran Ahmad, Mubashir Rehman, Mir Ali Shah (Pakistan Journal of Ophthalmology, 2019)
Purpose: To evaluate the effect of intra-vitreal bevacizumab in macular edema caused by branch retinal vein occlusion. Study Design: Interrupted time series study. Place and Duration of Study: Department of Ophthalmology Hayatabad Medical Complex, Peshawar and department of Ophthalmology Lady Reading Hospital Peshawar from 1st July 2016 to 31st December 2016. Material and Methods: There were 60 patients included in the study. All patients with macular edema due to BRVO visible clinically and evident on SD-OCT and visual acuity of less than 6/9 were included in the study. Patients who used other intra-vitreal drug for macular edema, those with surgery in the same eye and those with macular laser for macular edema were excluded from the study. All patients were given intra-vitreal 0.05 ml bevacizumab injection every month for 6 months. After 6 months OCT was repeated. At each monthly visit VA was measured and fundoscopy was done. Follow up of all patients was at six months. Results: Our study included 60 patients with mean age of 54.42 ± 9.19 years. The mean baseline central macular thickness was 427.06 µ with SD ± 63.54 µ. After 6 months significant improvement in visual acuity was documented. Also marked reduction in central macular thickness was noted after six months with mean of 327.44 µ with SD ± 55.55 µ. Conclusion: Intra-vitreal bevacizumab is an effective treatment for macular edema caused by BRVO in terms of both anatomic and visual improvement. Key words: Branch retinal vein occlusion, bevacizumab, macular edema.